Hybrid operation of triboelectric nanogenerator for electricity generation by a low‐temperature differential heat engine. (3rd February 2017) - Shaislamov, Ulugbek; Kim, Yeongmin; Kim, Won Sik; Jeong, Haejun; Lee, Heon‐Ju; Chun, Wongee
Summary: There are many types of triboelectric nanogenerators (TENGs) which differ in their operational modes (contact mode, sliding mode, etc.), converting mechanical energy into electrical energy. This paper introduces electricity generation from a small low‐temperature differential heat engine capable of utilizing low‐grade thermal energy. The engine is similar to the Gamma‐type Stirling engine and could run on temperature differentials ranging from 90 down to a few degrees Celsius. The work presented here gives technical details of how a small low‐temperature differential heat engine could be integrated with a TENG for electricity generation. Two different schemes were tested for the operation of TENG: one in non‐contact sliding mode and the other in vertical contact‐separation mode. For the temperature difference of 74.4 °C, the former delivered a maximum output voltage of 70 V whereas the latter resulted in 35 V. A maximum combined output voltage of 105 V was obtained capable of charging a 4.7 μF capacitor and discharged through LED lighting. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : This work presents the effective integration of triboelectric nanogenerators with a low‐temperature differential heat engine to harvest low‐grade thermal energy. Triboelectric nanogenerators, operating in two different modes, were capable of producing a combined output Voc of 105 V and Isc of 1.1 μA when the average difference between the hot and cold ends of the engine were 74.4°C.